COVID-19 and SARS-CoV-2: Despite the vaccination, new targets/drugs for treatment and the virus cycle mechanisms still have to be continually investigated - Victor GO Evangelho; Camila F Mattos; Marcia R Amorim; Juliana S Novais; Marcos K Veiga; Murilo L Bello; Helena C Castro (Open Journal of Proteomics and Genomics - Peertechz Publications, 2021)
Several countries are suffering with COVID-19 second wave that has been worse than the first one. In addition, new challenges are being imposed by new mutations and their high transmissibility, such as B.1.1.7, identified in the United Kingdom, and the strains P.1 and 501Y.V2, from Brazil and South Africa, respectively. They threaten the immune effects of the new launched vaccines (eg.: Coronavax, Oxford vaccine, and Sputnik) as nobody can assure their effectiveness against all coronavirus mutants that are still ahead. Finally, vaccination of the whole population against coronavirus, as it is done for influenza in the elderly people, is financially very difficult, especially in the low-income countries. Therefore, this brief 2-page opinion comes to highlight the fact that, similar to HIV infection (AIDS), COVID-19 will need continuous research about the virus cycle mechanisms and drug design/searching for new antivirus that may treat those infected with this still unknown virus to avoid its major effects and high lethality worldwide.